De-bottle necking Polyethylene Plant due to Butene shortage: A multi-attribute decision analysis using SMART - Handoko, Yulius; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2012)
The E.P Company supplies the customers with varieties of polyethylene products, to increase production capacity on the Low Linear Density Polyethylene (LLDPE) film grade, De-bottle necking in Reactor-2 (reactor dedicated to produce LLDPE grade) done by changing the condensing agent from Isohexane to Isopentane. Due to the production capacity and reliability on the reactor-2 increase, the demand for raw material Butene increase as Butene use as commonomer in the reactor-2 production. In other hand the Butene plant production decrease because of reduction of cooling capacity and efficiency, this condition create gap on the supply and demand for the Butene. The study objective to be achieved is to find the best solution to overcome Butene shortage problem to produce LLDPE polyethylene with considering the decision maker consideration and at optimize the cost. To achieve that objective, the SMART (Simple Multi Attribute Rating Technique) apply to enable decision maker to gain and increased understanding of his or her decision problem. To fulfill the gap on the supply and demand for Butene, a value tree is created, divided into two component cost and benefit. The study found that the best option for the company is to import Butene from outside (with the condition the new Butene sphere needs to be constructed). This option is recommended for implementation even thought it has the value of benefit at 2nd place (50.9), since a move to the option at 1st place (68.6) is expensive considering that each point increase in the value of benefits would cost $ USD 515,001.4 and at total $ USD 9,115,524/ year. This option also solves the problem, from attributes view. Keywords: multi-attribute decision analysis, Butene shortage, polyethylene plant